A comparative study on the effectiveness of De La Salle University-Manila's old and newly revised accountancy modular programs using selected factors of effectiveness - Alelis, Marc Christopher Gache (Animo Repository, 2022)
After 14 years, the Modular Program implemented in the Accountancy undergraduate program of De La Salle University - Manila has been strategically revised into a Newly Revised curriculum for the upcoming K-12 graduates. The main purpose of this study is to be able to compare the Old and Newly Revised Modular Programs of the Accountancy Program of De La Salle University - Manila by determining how factors of effectiveness (Academic Pressure, Pacing, and Personal Factors) in both programs affect the measurements of effectiveness (Academic Achievement, Knowledge Retention, and Satisfaction). A total of 48 and 108 students from ID 117 and ID 118 participated in this study. An analysis was executed through the use of descriptive statistics, Kolmogorov-Smirnov and Shapiro-Wilk tests of normality, Mann-Whitney U test, and regression analysis. The results showed that only the Academic Achievement had a significant change from the Old Modular Program to the Newly Revised Modular Program. As for the regression analysis, it was found that none of the variables had any relationship with one another for ID 117. On the other hand, the study provided that for the ID 118, Academic Pressure-Knowledge Retention, Academic Pressure-Satisfaction, Pacing-Knowledge Retention, Personal Factors-Academic Achievement, Personal Factors-Knowledge Retention, and Personal Factors-Satisfaction had significant relationships with each other.